Science Teaching and Learning: Qualitative and Functional Chemistry Education, Does Gender and Age Affect Academic Achievement - Ejimaji, Emmanuel Uwiekadom; Emekene, Clement Omanufoghor (Richtmann Publishing, 2011)
One of the key points in Late President Yar’adua’s 7- point agenda is the accomplishment of qualitative and functionalEducation. This can be monitored through assessing academic achievement of students. Chemistry Education occupies acentral position to all disciplines. This study examined the correlates between age and gender on academic achievement(CGPA) of Chemistry students. The study used thirty six (36) females and forty (40) males giving a total of sample seventy eight(76). Scatter – plot, mean and standard deviation were used for the descriptive statistics while univariate analysis of variance(ANOVA) and multiple regression were used for inferential statistics. T-test was used to test the null hypothesis formulated(P<0.05). Result revealed a linear relationship between, age-CGPA and gender-CGPA.A low positive correlation coefficientswas obtained for ages and gender (r=0.006 and 0.105) which were not significant. The predictor variables jointly accounted for1.1% of the variance, age was the better predictor. The null hypothesis tested was accepted implying no significant difference inacademic achievements of students. It was suggested that some more variables be included so as to determine significantcorrelation of students’ academic achievement of Chemistry students.